Innovation in Enterprises Operating at Informal Environments: The National Innovation Foundation, Lessons from India to Mexico - Rivera-Huerta René; Jaso-Sánchez Marco Aurelio; Ruiz-Castañeda Walter Lugo (SHS Web of Conferences)
In Latin America, the connection between innovative entrepreneurs in the informal economy and formal knowledge and policy institutions is minimal or non-existent. This is largely due to the fact that both academics and policymakers often assign a passive and therefore non-innovative role to such agents. However, this is not the case in other regions, particularly in India, where efforts are being made to enhance the capabilities of these entrepreneurs under the idea expressed by Anil Gupta that “minds in the margin are not marginal minds,” a lesson from which our society can learn [1]. This paper focuses on exploring the dynamics of the National Innovation Foundation, an intermediary organization in India that connects innovators in informal environments with the formal sector of their society, thereby strengthening their production while respecting their culture. The plausibility of applying this model to Mexico is also discussed.